2013
DOI: 10.1021/bi400557x
|View full text |Cite
|
Sign up to set email alerts
|

Function of Resistance Conferring Plasmodium falciparum Chloroquine Resistance Transporter Isoforms

Abstract: The function of P. falciparum chloroquine resistance transporter (PfCRT) can be quantified using a S. cerevisiae model system (Baro, N. K., Pooput C and Roepe P.D. Biochemistry. 50, 6701 – 6710). We further optimize this system to distinguish PfCRT isoforms found in P. falciparum strains and isolates from across the globe. We create and express 13 naturally occurring pfcrt alleles associated with a range of chloroquine resistant (CQR) phenotypes. Using galactose induction of PfCRT we quantify PfCRT and chloroq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
118
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(127 citation statements)
references
References 42 publications
9
118
0
Order By: Relevance
“…In resistant strains, the modified transporters are able to remove compound 1 from this vacuole. The mutated PfCRTa have altered amino acids in positions 72 to 76 (CVMNK in the wild type), depending on the geographical origin: CVIET for African and most Southeast Asian resistant strains versus SVMNT for the South American resistant strains (24,25). The hybrid compounds were initially tested in an IC 50 assay, determining the concentration required to inhibit the survival of 50% of parasites.…”
Section: Resultsmentioning
confidence: 99%
“…In resistant strains, the modified transporters are able to remove compound 1 from this vacuole. The mutated PfCRTa have altered amino acids in positions 72 to 76 (CVMNK in the wild type), depending on the geographical origin: CVIET for African and most Southeast Asian resistant strains versus SVMNT for the South American resistant strains (24,25). The hybrid compounds were initially tested in an IC 50 assay, determining the concentration required to inhibit the survival of 50% of parasites.…”
Section: Resultsmentioning
confidence: 99%
“…However, the existence of CQ-susceptible strains associated with the K76T mutation suggests that other genes could be involved in the resistance to CQ. The 76T mutation is necessary, but not sufficient, for influencing CQ susceptibility (22).…”
mentioning
confidence: 99%
“…2,8 Of the 53 isoforms, 11 are found in culture-adapted strains for which highly reproducible CQ IC 50 data quantifying CQ cytostatic potency are available. 9 However, the remaining isoforms are found in field isolates whose drug susceptibilities are typically determined via more qualitative single-pass assays, or not determined at all.…”
mentioning
confidence: 99%
“…9 Initial work with 11 PfCRT isoforms that are expressed in laboratory-cultured P. falciparum strains suggested that PfCRT mutations are necessary but not sufficient for the full shift in CQ IC 50 seen for these strains. 9 To further aid our understanding of the relative contribution of PfCRT isoforms to geographically disposed CQR phenotypes, in this paper we report on 45 of the currently known naturally occurring PfCRT isoforms.…”
mentioning
confidence: 99%